A non-obstructive gastric antral web case detected after upper gastrointestinal system bleeding - Akbaş, Enver; Altun, Reskan (AVES, 2019)
This is the first study on the construction of the relation-ship between a non-obstructive gastric antral web and gastric-outlet obstruction in children and adults.Congenital or acquired gastric antral webs (GAWs) may cause gastric-outlet obstruction in children and adults. Endoscopic methods are often used in the treatment of obstructive GAWs. We report the case of a patient with a congenital non-obstructive antral gastric web. The pa-tient was a 25-year-old male with gastrointestinal hem-orrhage followed by dyspeptic complaints. There was a follow-up period for the patient after treatment. Because GAWs are encountered and rarely reported in the litera-ture, the images taken during endoscopic surgery of the patient, as a significant contribution to the literature, are also presented.
Keywords: Non-Obstructive Gastric; Upper Gastrointestinal System; Web Case